Children foster care law and practice: What Malaysia can learn from foster care (Ihtidhan) in Jordan - Mohd, Azizah; A. Kadir, Nadhilah (International Islamic University Malaysia, 2014)
Foster care is one of the means of child protection in Malaysia and in many other countries like Singapore, Australia, United Kingdom, Algeria, Egypt and Morocco. This is also highlighted in international legal documents like the United Nations Convention of the Rights of the Child (the CRC) which also recognise the Islamic law concept of foster care (kaffalah). Through foster care, a child is placed either in an institution or fostered by individual foster parents. This paper aims at examining the law and practice of individual foster care in Malaysia with a comparative overview of the law and practice in Jordan. The comparison is intended to assist development of better law and practice of foster care in Malaysia where suitable, relevant and necessary. Analysis focuses on certain suitable law and practice of foster care in Jordan i.e. what Malaysia can learn from foster care in Jordan. The research is basically library research. A minor part of the research also involves interview of relevant officers on certain practices that are not documented. It is hoped that this paper will provide good suggestions for better protection of children in Malaysia through foster care.